A novel approach for the production of green biosurfactant from Pseudomonas aeruginosa using renewable forest biomass - Hrůzová, Kateřina; Patel, Alok; Masák, Jan; Maťátková, Olga; Rova, Ulrika; Christakopoulos, Paul; Matsakas, Leonidas (The Science of the total environment, 2020)
The rising demand for surfactants by the pharmaceuticals and cosmetic industries has generated vast amounts of petroleum-based synthetic surfactants, which are often toxic and non-degradable. Owing to their low toxicity, stability in extreme conditions, and biodegradability, biosurfactants could represent a sustainable alternative. The present study aimed to maximize the production of rhamnolipids (RL) from Pseudomonas aeruginosa by optimizing glucose concentration, temperature, and C/N and C/P ratios. After 96 h of cultivation at 37 °C, the final RL concentration was 4.18 ± 0.19 g/L with a final yield of 0.214 ± 0.010 g/gglucose when pure glucose was used as a carbon source. At present, the main obstacle towards commercialization of RL production is economic sustainability, due to the high cost of downstream processes and media components. For this reason, a renewable source such as wood hydrolysates (from birch and spruce woodchips) was examined here as a possible source of glucose for RL production. Both hydrolysates proved to be adequate, resulting in 2.34 ± 0.17 and 2.31 ± 0.10 g/L of RL, respectively, and corresponding yields of 0.081 ± 0.006 and 0.089 ± 0.004 g/gsugar after 96 h. These results demonstrate the potential of using renewable biomass for the production of biosurfactants and, to the best of our knowledge, they constitute the first report on the use of wood hydrolysates for RL production.
Keywords: Organosolv fractionation; Biosurfactants; lesy; Pseudomonas; Wood hydrolysate; glykolipidy; ropa; povrchově aktivní látky; Biomass; Glycolipids; Rhamnolipid; Surface-Active Agents; Forests; Petroleum; biomasa; Pseudomonas aeruginosa